On the Origins of “Hostless” Supernovae: Testing the Faint-end Galaxy Luminosity Function and Supernova Progenitors with Events in Dwarf Galaxies - Louis-Gregory Strolger; Mia Sauda Bovill; Eric Perlman; Craig Kolobow; Conor Larison; Zachary G. Lane (The Astrophysical Journal, 2025)
We present arguments on the likely origins of supernovae without associated host galaxies from open field, nonclustered environments. We show why it is unlikely these “hostless” supernovae stem from escaped hypervelocity stars in any appreciable numbers, or the extreme outer halos of large galaxies, especially for core-collapse supernovae. It is highly likely that hostless events arise from dwarf host galaxies too faint to be detected in their parent surveys. Several detections and numerous upper limits suggest a large number of field dwarfs, to M _V  > −14, which themselves may be important to constraining the slope of the low-mass end of the UV luminosity function, understanding galaxy evolution, and putting Lambda cold dark matter (ΛCDM) into context. Moreover, the detailed study of these mass- and metallicity-constrained host environments, and the variety of supernovae that occur within them, could provide more stringent constraints on the nature of progenitor systems.